Інформаційне забезпечення економічної безпеки бізнес-процесів підприємства торгівлі - Коптєва (Фадєєва), Ганна Миколаївна (My University, 2020)
Використання інформаційного забезпечення економічної безпеки бізнес-процесів обумовлює зростання швидкості та адекватності процесу прийняття управлінських рішень відповідальними й споживачами бізнес-процесів, покращення показників ефективності підприємства торгівлі та укріплення його позиції на ринку, тому парадигму процесного підходу до забезпечення економічної безпеки прийнято за базову під час удосконалення інформаційного забезпечення управління бізнес-процесами підприємства торгівлі. Отже, з урахуванням вимог сучасного бізнес-середовища підвищуються вимоги до якості інформаційного ресурсу, а саме інформаційного забезпечення економічної безпеки торговельного підприємства. Автором статті визначено роль інформаційного забезпечення в комплексній системі економічної безпеки бізнес-процесів підприємства торгівлі. Запропоновано схему інформаційного забезпечення економічної безпеки бізнес-процесів підприємства торгівлі.

The use of information support for the economic security of business processes leads to an increase in the speed and adequacy of the process of making managerial decisions by responsible and consumers of business processes, improving the efficiency of the trading enterprise and strengthening its position in the market. Therefore, the paradigm of the process approach to ensuring economic security is accepted as the basic one when improving the information support for managing business processes of a trade enterprise. Consequently, taking into account the requirements of the modern business environment, the requirements for the quality of an information resource, namely, information support for the economic security of a commercial enterprise, are increasing. The author of the article defines the role of information support in the complex system of economic security of business processes of a trade enterprise and offers a definition of this economic category. Information support of economic safety of business processes of an enterprise is a collection of forms of documents, regulations, scorecards, indicators and methods of evaluation of economic security and management decisions on the amounts and forms of existence that are used in the information system of trade enterprise. Taking into account the specifics of modern threats, in our opinion, the task of information support is not only information support of the level of economic security of business processes of a trade enterprise, but also the formation of information flows between responsible and consumers of business processes and security objects, external and internal environment. To develop information support for economic security with a process approach in the management of an economic object, its main business processes are defined, taking into account the specifics of the trade enterprise. The scheme of information support of economic security of business processes of the trade enterprise is offered. As a result of forming arrays of information, selecting methods for its processing and modeling, certain indicators (financial and non-financial) are obtained that characterize the state of economic security of business processes in the enterprise.
Information support of economic security of business processes of the trade enterprise
Keywords: управлінські рішення; економіка; інформатизація; information security; economic security of the enterprise; business processes of the trade enterprise